Low-intensity laser therapy effect on the recovery of traumatic spinal cord injury - Paula, Alecsandra Araujo; Nicolau, Renata Amadei; Lima, Mario de Oliveira; Castillo Salgado, Miguel Angel [UNESP]; Cogo, Jose Carlos (Springer, 2014)
Scientific advances have been made to optimize the healing process in spinal cord injury. Studies have been developed to obtain effective treatments in controlling the secondary injury that occurs after spinal cord injury, which substantially changes the prognosis. Low-intensity laser therapy (LILT) has been applied in neuroscience due to its anti-inflammatory effects on biological tissue in the repairing process. Few studies have been made associating LILT to the spinal cord injury. The objective of this study was to investigate the effect of the LILT (GaAlAs laser-780 nm) on the locomotor functional recovery, histomorphometric, and histopathological changes of the spinal cord after moderate traumatic injury in rats (spinal cord injury at T9 and T10). Thirty-one adult Wistar rats were used, which were divided into seven groups: control without surgery (n = 3), control surgery (n = 3), laser 6 h after surgery (n = 5), laser 48 h after surgery (n = 5), medullar lesion (n = 5) without phototherapy, medullar lesion + laser 6 h after surgery (n = 5), and medullar lesion + laser 48 h after surgery (n = 5). The assessment of the motor function was performed using Basso, Beattie, and Bresnahan (BBB) scale and adapted Sciatic Functional Index (aSFI). The assessment of urinary dysfunction was clinically performed. After 21 days postoperative, the animals were euthanized for histological and histomorphometric analysis of the spinal cord. The results showed faster motor evolution in rats with spinal contusion treated with LILT, maintenance of the effectiveness of the urinary system, and preservation of nerve tissue in the lesion area, with a notorious inflammation control and increased number of nerve cells and connections. In conclusion, positive effects on spinal cord recovery after moderate traumatic spinal cord injury were shown after LILT.
Keywords: Low-intensity laser therapy; Spinal cord injury; Nerve regeneration